2012
DOI: 10.1111/j.1469-1795.2012.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Females first? Past, present and future variability in offspring sex ratio at a temperate sea turtle breeding area

Abstract: The long-term survival of species with temperature-dependant sex determination requires a sufficient range of incubation temperatures to ensure that both males and females are produced. The primary sex ratio of sea turtles is determined by the temperature experienced by eggs during the middle third of incubation. Here, we investigated the variability in the production of male and female offspring by loggerhead sea turtles Caretta caretta at six nesting beaches in the temperate breeding area of Zakynthos, Greec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…This has led to speculation that nesting females could compensate for the effects of climate change by continuing to locate microhabitats that maximize fitness (Mitchell et al ., ; Telemeco et al ., , ). The sandy, sun‐exposed beaches upon which sea turtles nest can experience high temperatures (Tapilatu & Tiwari, ; Katselidis et al ., ), but we do not yet understand whether maternal nest‐site selection could compensate for temperature increases under climate change. Data from other, smaller reptile species that dig shallower nests suggest that morphological constraints on the ability to dig deeper nests could limit potential adaptive responses to climate change, and lead to skewed sex ratios and increased embryonic mortality (Mitchell et al ., ; Katselidis et al ., ; Telemeco et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to speculation that nesting females could compensate for the effects of climate change by continuing to locate microhabitats that maximize fitness (Mitchell et al ., ; Telemeco et al ., , ). The sandy, sun‐exposed beaches upon which sea turtles nest can experience high temperatures (Tapilatu & Tiwari, ; Katselidis et al ., ), but we do not yet understand whether maternal nest‐site selection could compensate for temperature increases under climate change. Data from other, smaller reptile species that dig shallower nests suggest that morphological constraints on the ability to dig deeper nests could limit potential adaptive responses to climate change, and lead to skewed sex ratios and increased embryonic mortality (Mitchell et al ., ; Katselidis et al ., ; Telemeco et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Katselidis et al (2012), studying long-term variation of hatchling sex ratios from loggerhead turtle nests at Zakynthos, Greece, showed that males and females were produced at different times within a season and that some beaches were responsible for male production, while females were produced on other beaches. Understanding the range of male versus female offspring production within a rookery may be critical for specific management actions at each nesting beach.…”
Section: Unknown Sources Of Mortalitymentioning
confidence: 99%
“…Some authors suggest that turtles start their migration due to a temperature cue and then nest soon after arriving at their nesting grounds (Mazaris et al, 2009), while others suggest that turtles arrive early at the nesting beaches (Eckert and Eckert, 1988;Pike, 2009) in order to mate with males and complete the development of their first clutch of eggs (Schofield et al, 2013). The cues would then be at the nesting grounds, where they would wait to nest when the environmental conditions are optimal (Eckert and Eckert, 1988;Katselidis et al, 2012;Pike, 2009). This is confounded further due to findings that some leatherback populations engage in foraging excursions during their internesting interval (Byrne et al, 2009;Georges et al, 2007), potentially encountering temperature or resource cues not considered before.…”
Section: Introductionmentioning
confidence: 97%
“…Phenological shifts might also mean that developing nests now face a potentially different set of conditions such as temperature and rainfall, which will determine their sex ratios (Ackerman, 1997;Hays et al, 2010;Katselidis et al, 2012) and hatching success (Miller, 1997;Saba et al, 2012). In addition, since hatchlings disperse after emergence mostly due to passive drift on oceanic currents, which change at different times of the year, phenological shifts may alter their spatial fate and possible survival (Blanco, 2010;Gaspar et al, 2012;Shillinger et al, 2012).…”
Section: Introductionmentioning
confidence: 98%